Przykłady zastosowań metod dekompozycyjnych w badaniach marketingowych - Bąk, Andrzej (Examples of applications of decompositional methods in marketing research, 2005)
Stated consumer preferences refer to hypothetical market behavior of consumers. In this case the analytical methods are based on data collected a p r io r i by means of surveys to register intentions stated by consumers at the moment of survey taking. The methods used for stated preference analysis include conjoint analysis and discrete choice methods. In this paper outlines of both groups methods are given. Next, two examples of their application in marketing research are discussed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 27-41